Increased Expression of Toll-Like Receptor (TLR) 2 and TLR6 on Peripheral Blood Monocytes by Induction of Staphylococcal Enterotoxin B During Exacerbation of Atopic Dermatitis Patients - Salim F; Gunawan H; Suwarsa O; Sutedja E (Dove Medical Press, 2023)
Fitria Salim,1,2 Hendra Gunawan,3 Oki Suwarsa,3 Endang Sutedja3 1Doctoral Study Program, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia; 2Department of Dermatology and Venereology, Faculty of Medicine, Universitas Syiah Kuala, Banda Aceh, Indonesia; 3Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran-Hasan Sadikin General Hospital, Bandung, West Java, IndonesiaCorrespondence: Fitria Salim, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Syiah Kuala - Zainoel Abidin General Hospital, Kopelma Darussalam, Banda Aceh, Aceh, 23111, Indonesia, Tel +65151977, Fax +65152053, Email fitria.spkk@gmail.comBackground: Atopic dermatitis (AD) is a chronic and recurrent inflammatory skin disease that can be triggered by various precipitating factors, including colonization by Staphylococcus aureus (S. aureus). The toll-like receptor (TLR), which belongs to the family of pattern recognition receptors (PRR), can recognize components of S. aureus, such as staphylococcal enterotoxin B (SEB). This receptor is known to be expressed on monocytes. However, the understanding of the role of SEB in the pathogenesis of AD through the TLR pathway, especially TLR2 and TLR6, is not widely known.Purpose: To investigate the expression of TLR2 and TLR6 on peripheral blood monocytes induced by SEB during AD exacerbations.&#x00A0Patients and Methods: Twenty AD patients and 20 healthy subjects as a control group were selected. A 5 mL blood sample from each subject was taken for monocyte culture, which was induced by SEB for three days, and the outcomes were assessed by flow cytometry to evaluate TLR2 and TLR6 expression.Results: The expression of TLR2 on peripheral blood monocytes in AD patients was increased compared to healthy controls (p = 0.000), but not for the expression of TLR6 (p = 0.304). In the AD group, TLR2 and TLR6 expression on peripheral blood monocytes after being induced by SEB was significantly increased compared to before induction (p = 0.025 and p = 0.023, respectively), but not in the control group (p = 0.737 and p = 0.100, respectively).Conclusion: There is significantly increased expression of TLR2 and TLR6 on peripheral blood monocytes induced by SEB during exacerbation in AD patients.Keywords: atopic dermatitis, monocyte, staphylococcal enterotoxin B, TLR2, TLR6